2022
DOI: 10.3390/su14042389
|View full text |Cite
|
Sign up to set email alerts
|

Leaders’ Emotion Regulation and the Influence of Respect and Entitlement on Employee Silence

Abstract: Although numerous researchers have examined leaders’ behavior in promoting employee voice, so far, there have been limited empirical studies in interpersonal emotion regulation (IER) and employee silence literature. This study aims to investigate how leaders’ IER can break the barrier of employee silence through examining the mediating roles of perceived mutual recognition respect and psychological entitlement. To enhance sustainable organization practices, this may be the first study that identifies leaders’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…When leaders effectively manage their own emotions and those of their subordinates and show care and support to their subordinates, subordinates are more engaged in their work and reward the organization. This confirms the insight that “leadership emotions are a deeper factor in employee engagement than employee emotions” [ 6 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…When leaders effectively manage their own emotions and those of their subordinates and show care and support to their subordinates, subordinates are more engaged in their work and reward the organization. This confirms the insight that “leadership emotions are a deeper factor in employee engagement than employee emotions” [ 6 ].…”
Section: Discussionsupporting
confidence: 80%
“…In particular, leaders, as an important aspect of the work environment, often have significant impacts on subordinates’ emotions. Therefore, leaders’ emotions and emotion regulation strategies are one of the key causes of subordinates’ emotions, attitudes and behaviors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, silence is a safe way to protect resources (Xu et al ., 2015). Employees will choose more silence and less voice to avoid potential resource threats when supervisors do not respect them (Khan et al ., 2022).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…By examining the relationship between them, this study will provide practical value for the intervention of employee's voice and silence. On the other hand, stressors such as perceived unfairness and disrespect have been found to be associated with employees' voice and silence (De Clercq and Pereira, 2023; Khan et al ., 2022). Since illegitimate tasks convey unfairness and disrespect information (Schulte-Braucks et al ., 2019; Semmer et al ., 2015), it may be potentially related to employees' voice and silence.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is the general expectation from marriage or our society that partners tend to impose on each other characteristics that become the cause of burden or stress (Umubyeyi & Mtapuri., 2019). According to a recent analysis, it has been indicated that the divorce rate is around 4.08 per 1000 marriages across the world (Khan et al, 2022). In Pakistan, according to a recent survey around 69 percent of the population is married and 0.58% are being divorced due to different reasons that are enhancing with the passage of time (Ahmad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%